Appropriate Primer Selection Improves Molecular Bird Sexing Accuracy - Fauziah Fitriana; Mas Farouq Uz Zaman Al Qodry; Juan Carlos Greevins De Lucas; Dian Ritma Setyorini; Fatkhanuddin Aziz (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
Birds sexing utilize the Polymerase Chain Reaction (PCR) technique is increasingly being used by researchers and breeders. The PCR technique has high sensitivity, but its success is influenced by the specificity of the DNA template with the oligo primer used. This study aimed to evaluate 5 types of PCR primers P2/P8, 2550F/2718R, CHD1F/CHD1R, 1237L/1272H, and CHD1LF/CHD1LR to determine the sex of Phasianidae, Anatidae, Muscicapidae, and Psittacidae families. This research was conducted by tested primers mentioned above to amplify the target gene chromodomain helicase DNA binding 1 (CHD1) on DNA samples of each pair of males and females from four bird families, respectively. The results indicated that CHD1LF/CHD1LR PCR primer gave the best results and was recommended to determine the sex of four families tested. Some of other primers tested in this study failed to amplify targeted gene correctly, it is important to use appropriate primer to increase bird sexing accuracy.